Clinical Outcome of Pott’s Spine with Twelve Months of Chemotherapy - Thapa, Bishnu Babu; Shah, Rajesh Pratap (Nepal Orthopaedic Association Journal, 2020)
Introduction: Chemotherapy remains the mainstay of treatment of Pott’s Spine. There is lack of consensus regarding the duration and regime of chemotherapy. This study aims to see the clinical outcome of Pott’s Spine treated with 12 months, 3HRZE and 9HR, of chemotherapy.Methods: This is a prospective study conducted at Shree Birendra Hospital from 2011 to 2018. A total of forty five pott’s spine patients were diagnosed and started chemotherapy. They were diagnosed clinicoradiologically and biopsy was done only in eight patients. All patients were treated with 12 months of chemotherapy, 3HRZE and 9HR, irrespective of conservative or surgical treatment. During this period only thirty seven patients were completed chemotherapy from our centre and they were included in our study. They were followed up for 12 months. Data were analysed in SPSS version 21.Results: Out of 45 patients, a total of 37 patients were completed 12 months chemotherapy and followed up. Out of 37 patients 25 were treated conservatively and rest were operatively along with chemotherapy. 19 patients had thoracic & thoracolumbar infection and 18 had lumbar infection. All the patients were improved clinicoradiologically.Conclusion: All the Pott’s Spine patients were improved clinicoradiologically with 12 months of Chemotherapy.